Enhancing progressive collapse resistance of steel structures using a new bolt sleeve device - Shaheen, Mohamed A.; Atar, Muhammed; Cunningham, Lee S. (Elsevier Sci Ltd, 2023)
In the present study, frame robustness is enhanced by improving the contribution of the bolts to the rotational capacity of connections; the higher the bolts' elongation, the higher the rotational capacity that can be achieved. The proposed method comprises a hollow steel sleeve, with a predetermined wall curvature, that is inserted between the washer and the end plate interrupting the load path in the connection thus enabling a more ductile response. In order to demonstrate the efficacy of the proposed method, end plate connections with varying sleeve parameters are numerically examined using verified FE models. The proposed system significantly increases the ductility and strength of the connection by up to 2.6 and 2.5 times that of the standard connection, respectively. Additionally, different ductile responses can be achieved based on the sleeve parameters without changing the configuration of the connection.
Keywords: Catenary action; Ductility; Progressive collapse; Robustness; Rotational capacity; Sleeve